Pengalaman Bidan Memberikan Penyuluhan Tentang Ante Natal Care Pada Ibu Hamil Di Puskesmas Di Kota Padangsidimpuan - Ganti Tua Siregar; Ramlan Nasution; Herawati Harahap (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Supervision and care during pregnancy is something that is important to do for the survival of the mother and the baby to be born. Antenatal care (ANC) is a pregnancy examination to optimize the mental and physical health of pregnant women. So that they are able to deal with childbirth, the postpartum period, preparation for breastfeeding and the return of reproductive health in a natural way. This study was conducted to determine the experience of midwives in providing counseling about ante natal care to pregnant women at the Puskesmas in Padangsidimpuan City. The research design is phenomenology. The method of data collection was carried out by in-depth interviews. Purposive sampling method was used to select participants who met the criteria as participants. Participants involved in this study were midwives who worked at the Puskesmas in Padangsidimpuan City, totaling 3 people. The results of the interviews were transcribed and analyzed using the Collaizi method and obtained 5 themes, namely: 1) The motivation of midwives to provide counseling, 2) Obstacles faced by midwives in providing counseling, 3) Strategies to motivate pregnant women to participate in counseling, 4) Responses of pregnant women after receiving counseling , and 5) Support from health institutions for puskesmas activities. Keywords: Midwife, counseling, pregnant women